New Relation-Theoretic Fixed Point Theorems in Revised Fuzzy Metric Spaces With an Application to Fractional Differential Equations - Muraliraj, A.; Thangathamizh, R. (Communications in Mathematics and Applications, 2023)
In this paper, we introduce the notion of revised fuzzy \(\mathcal{R}\)-\(ψ\)-contractive mappings and prove some relevant results on the existence and uniqueness of fixed points for this type of mappings in the setting of non-Archimedean revised fuzzy metric spaces. Several illustrative examples are also given to support our newly proven results. Furthermore, we apply our main results to prove the existence and uniqueness of a solution for Caputo fractional differential equations.